The Tragedy of the Athenian Ideal in Thucydides and Plato - Hogan, John T. (Greek studies., 2020)
This book shows how Plato's Statesman and Thucydides' presentation of the moral collapse in Athenian political discourse reveal many points of agreement between Plato and Thucydides.